2022
DOI: 10.1038/s41531-022-00351-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral and gut dysbiosis leads to functional alterations in Parkinson’s disease

Abstract: Although several studies have identified a distinct gut microbial composition in Parkinson’s disease (PD), few studies have investigated the oral microbiome or functional alteration of the microbiome in PD. We aimed to investigate the connection between the oral and gut microbiome and the functional changes in the PD-specific gut microbiome using shotgun metagenomic sequencing. The taxonomic composition of the oral and gut microbiome was significantly different between PD patients and healthy controls (P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…At that point, several studies were able to identify a distinct gut microbial composition in PD. Jo et al [ 113 ] furthered the research on the microbiome by studying the functional alteration of the microbiome in PD. The taxonomic oral and gut microbiome profile significantly differed between PD patients and healthy controls, with a higher abundance of Lactobacillus and opportunistic pathogens [ 113 ].…”
Section: Microbial Dysbiosis and α-Synmentioning
confidence: 99%
See 1 more Smart Citation
“…At that point, several studies were able to identify a distinct gut microbial composition in PD. Jo et al [ 113 ] furthered the research on the microbiome by studying the functional alteration of the microbiome in PD. The taxonomic oral and gut microbiome profile significantly differed between PD patients and healthy controls, with a higher abundance of Lactobacillus and opportunistic pathogens [ 113 ].…”
Section: Microbial Dysbiosis and α-Synmentioning
confidence: 99%
“…Jo et al [ 113 ] furthered the research on the microbiome by studying the functional alteration of the microbiome in PD. The taxonomic oral and gut microbiome profile significantly differed between PD patients and healthy controls, with a higher abundance of Lactobacillus and opportunistic pathogens [ 113 ]. Functional analysis revealed a down-regulation of microbial glutamate and arginine biosynthesis gene markers and an up-regulation of antibiotic resistance gene markers in PD patients compared to healthy controls [ 113 ].…”
Section: Microbial Dysbiosis and α-Synmentioning
confidence: 99%
“…108 Many studies have suggested that environmental risk factors or other risk factors accumulated in the gut would penetrate to the brain and promote neurodegeneration diseases such as Parkinson's disease, Alzheimer's disease, and autism spectrum disorders. 111–120 Kim et al came up with a modular microfluidic device, on which co-cultured gut epithelial cells and brain endothelial cells develop the GBA track on a chip (Fig. 7b).…”
Section: Multi-organ Chips For Investigating the Entry Of Risk Factor...mentioning
confidence: 99%
“…Concerning PD, oral features associated with the disease such as dysphagia, salivary pH and drooling may influence the oral microbiota by altering the β-diversity index and favoring the growth of opportunistic oral microbes and Lactobacillus species, which may exacerbate the clinical symptoms and correlate with worse Hamilton Anxiety Scale and Hamilton Depression Rating Scale scores [ 70 , 496 , 497 ]. Moreover, combined oral-gut microbiome metagenomic sequencing revealed a link between oral Lactobacillus and gut opportunistic pathogens, suggesting a connection between these two microbial communities [ 498 ]. Other oral microbial species whose abundance has been found altered in PD patients are: Actinomyces AFQC_s , Scardovia , Kingella oralis , Streptococcus mutans , Veillonella AFUJ_s , Prevotella , Firmicutes , Negativicutes (all increased) and Lachnospiraceae AM420052_s , Treponema KE332528_s , Proteobacteria , Tenercutes and Pastescibacteria (all decreased) [ 499 , 500 ].…”
Section: Oral and Nasal Microbiota: Other Important Districts Involve...mentioning
confidence: 99%